1998
DOI: 10.1017/s0266466698143049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Shift in the Trend Function on Dickey–fuller Unit Root Tests

Abstract: This article analyzes the asymptotic behavior of the Dickey–Fuller unit root tests when the variable is generated under the breaking trend hypothesis. Our results show that the asymptotic behavior of these statistics allows for the rejection of the unit root hypothesis. This asymptotic finding contrasts with the results that can be found in the literature devoted to the analysis of the integration order of a variable in the presence of a structural break. However, some Monte Carlo exercises show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…Perron (2006Perron ( , 1989 reported that standard tests for stationarity ("unit root tests")-such as the augmented Dickey-Fuller test (Said & Dickey, 1984), Phillips-Perron test (Phillips & Perron, 1988), and others-will generally fail to reject the null hypothesis of nonstationarity when applied to a time series that is broken TS. Monte Carlo simulation experiments indicate that in this case, such tests suffer from low power and thus are biased in favor of concluding that a time series is nonstationary (Lee, Huang, & Shin,1997;Montañés & Reyes, 1998Perron, 1989Perron, , 1994. A similar bias in favor of finding nonstationarity has also been shown to apply to tests with a null hypothesis of stationarity (Kwiatkowski, Phillips, Schmidt, & Shin, 1992).…”
Section: Authors' Notementioning
confidence: 99%
“…Perron (2006Perron ( , 1989 reported that standard tests for stationarity ("unit root tests")-such as the augmented Dickey-Fuller test (Said & Dickey, 1984), Phillips-Perron test (Phillips & Perron, 1988), and others-will generally fail to reject the null hypothesis of nonstationarity when applied to a time series that is broken TS. Monte Carlo simulation experiments indicate that in this case, such tests suffer from low power and thus are biased in favor of concluding that a time series is nonstationary (Lee, Huang, & Shin,1997;Montañés & Reyes, 1998Perron, 1989Perron, , 1994. A similar bias in favor of finding nonstationarity has also been shown to apply to tests with a null hypothesis of stationarity (Kwiatkowski, Phillips, Schmidt, & Shin, 1992).…”
Section: Authors' Notementioning
confidence: 99%
“…1 See also Montañés and Reyes (1998 who examined the asymptotic behavior of the Augmented Dickey-Fuller test (Dickey and Fuller, 1979;Said and Dickey, 1984) and the Phillips-Perron (Phillips and Perron, 1988) test under the crash alternative hypothesis. Leybourne et al (1998) and Leybourne and Newbold (2000) analyzed the effect of a break on a standard DF test under the unit root null hypothesis and showed that size distortions can occur, especially when the break is early in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Nunes et al (1997), Montañés and Reyes (1998), Leybourne et al (1998), Lee and Strazicich (2001) and Sen (2008) found that unit root tests spuriously reject the unit root null when there is a break under the null hypothesis.…”
Section: A Number Of Tests Have Been Developedmentioning
confidence: 99%